2021
DOI: 10.1590/1414-431x202010022
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a predictive factor for chronic kidney disease in adults: systematic review and meta-analysis

Abstract: Chronic kidney disease (CKD) is one of the main chronic diseases affecting the world population due to its high prevalence and increasing morbidity. Similarly, obesity gained the interest of the scientific community as it directly or indirectly increases mortality from cardiovascular causes, and its prevalence characterizes a pandemic. The objective of this study was to investigate obesity measured by body mass index as a predictor for end-stage renal disease in the general adult population. A systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
(31 reference statements)
0
10
0
1
Order By: Relevance
“…Obesity-related chronic kidney disease (OB-CKD) is receiving increasing attention because of the obesity pandemic [ 1 3 ]. OB-CKD is characterized by glomerular hypertrophy and microalbuminuria, which are also markers of systemic vascular endothelial cell lesions that involve renal arteries and glomerular endothelial cells [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity-related chronic kidney disease (OB-CKD) is receiving increasing attention because of the obesity pandemic [ 1 3 ]. OB-CKD is characterized by glomerular hypertrophy and microalbuminuria, which are also markers of systemic vascular endothelial cell lesions that involve renal arteries and glomerular endothelial cells [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…25 However, Pinto, et al (2021) found that people with obesity had a 1.81 times higher risk of developing CKD (OR = 1.81, 95% CI = 1.52-2.16). 26 The experimental research using rats by Salim et al (2018) showed that a high-fat diet, which results in obesity, could damage the kidney by contributing to glomerulosclerosis, tubular defects, inflammation, and other histopathological changes in the 27 Chang, et al (2018) explained that the measured BMI did not fully represent the variation in the composition of each body. Therefore, BMI was not accurate enough to determine its effect on CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with a low-grade inflammatory state, oxidative stress, abnormal lipid metabolism, activation of the renin-angiotensin-aldosterone system and increased insulin production, including accumulation of ectopic lipids and increased deposition of renal sinus fat. These different effects lead to specific pathological changes in the kidney that may be responsible for the higher risk of CKD seen in observational studies (7,9).…”
Section: Discussionmentioning
confidence: 99%